DETERMINAN KEPUTUSAN INVESTASI SAHAM SYARIAH PADA INVESTOR MILENIAL DI JOMBANG: PERAN KEMUDAHAN AKSES INFORMASI DIGITAL DAN PERSEPSI RISIKO DENGAN PENDEKATAN STRUCTURAL EQUATION MODELING - PARTIAL LEAST SQUARE (SEM-PLS) - Beni Sucipto (STIE PGRI Dewantara Jombang, 2022)
This study aims to analyze the influence of ease of access to digital information and risk perception on sharia stock investment decisions among millennial investors in Jombang. The increasing number of millennial investors in Indonesia’s Islamic capital market highlights the need to understand the factors influencing their investment decisions, especially in the digital era where access to information is easier but also accompanied by various risks. This research adopts a quantitative approach using the Structural Equation Modeling – Partial Least Square (SEM-PLS) method with SmartPLS Version 4 as the analytical tool. The population consists of millennial investors registered in the Sharia Investment Gallery (GIS) and investor communities in the Jombang area. The sampling technique employed is purposive sampling with criteria including individuals aged 20–40 years (millennial category), those who have invested in sharia stocks, and those residing in Jombang. The total sample size is 90 respondents. Data were collected through the distribution of online questionnaires using Google Forms. The variables examined in this study include ease of access to digital information, risk perception, and sharia stock investment decisions. Data analysis using SmartPLS Version 4 includes evaluation of the outer model (convergent and discriminant validity tests, as well as reliability tests using composite reliability and Cronbach’s alpha) and evaluation of the inner model (R-square, Q-square, and hypothesis testing using path coefficients, T-statistics, and P-values). The results indicate that ease of access to digital information and risk perception have a positive and significant effect on sharia stock investment decisions among millennial investors in Jombang. These findings suggest that the easier the access to digital information and the better the investors’ risk perception, the more prudent their investment decision-making.